2009
DOI: 10.1063/1.3126964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local E×B flow shear on the stability of magnetic islands in tokamak plasmas

Abstract: The influence of local E ϫ B flow shear on a relatively wide, constant-, magnetic island embedded in a large-aspect-ratio, low-␤, circular cross-section tokamak plasma is examined, using a slab approximation to model the magnetic geometry. It is found that there are three separate solution branches characterized by low, intermediate, and high values of the shear. Flow shear is found to have a stabilizing effect on island solutions lying on the low and high shear branches, via a nonlinear modification of the io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Ofman et al and Chen et al have shown that the shear flow could effectively decrease the saturated magnetic island width when the velocity of the shear flow is below the Alfvén speed [20,21]. Fitzpatrick and Waelbroeck examined the influence of the local × E B flow shear on the magnetic island [23], in which the stabilizing effect of velocity shear is in accordance with the previous result in [20,21]. Chandra et al investigated the influence of the toroidal flow on the tearing mode instability in toroidal geometry, indicating that the toroidal flow has a stabilizing effect due to the modification in the q-profile arising from a flow induced 'Shafranov' like shift [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Ofman et al and Chen et al have shown that the shear flow could effectively decrease the saturated magnetic island width when the velocity of the shear flow is below the Alfvén speed [20,21]. Fitzpatrick and Waelbroeck examined the influence of the local × E B flow shear on the magnetic island [23], in which the stabilizing effect of velocity shear is in accordance with the previous result in [20,21]. Chandra et al investigated the influence of the toroidal flow on the tearing mode instability in toroidal geometry, indicating that the toroidal flow has a stabilizing effect due to the modification in the q-profile arising from a flow induced 'Shafranov' like shift [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is thought that turbulence will have a significant effect on the stability of the mode [6,7,8]. The current profile can be modified by the presence of the island itself and flattening of density and temperature profiles in island vicinity.…”
Section: Introductionmentioning
confidence: 99%
“…Contributions to the current density come from various sources, including the induced current [2], bootstrap current [3,4] and polarization current [5]. Furthermore, it is thought that turbulence will have a significant effect on the stability of the mode [6][7][8]. The current profile can be modified by the presence of the island itself and flattening of density and temperature profiles in island vicinity.…”
Section: Introductionmentioning
confidence: 99%
“…[17] On the other hand, the toroidal plasma flow can delay the evolution of DTMs, [28] and the suppression effect depends on the magnitude of flow velocity and its shear rate on the rational surfaces. [29][30][31][32] The toroidal flows can affect the dynamics of magnetic islands through the coupling of magnetic curvature with pressure and density. [33] In order to investigate the influence of local toroidal flow (LTF) on DTMs, the reduced MHD (RMHD) simulation method is used to study the evolution of DTMs in various LTF cases in this work.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] On the other hand, the toroidal plasma flow can delay the evolution of DTMs, [ 28 ] and the suppression effect depends on the magnitude of flow velocity and its shear rate on the rational surfaces. [ 29–32 ] The toroidal flows can affect the dynamics of magnetic islands through the coupling of magnetic curvature with pressure and density. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%